How Effective Diabetic Foot Care is in Preventing Ulcers: Literature Review - Davit Hermansyah; Sri Wahyuni; Dwi Retno Sulistyaningsih; Ahmad Ikhlasul Amal (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetic foot ulcers are a serious complication of diabetes that can lead to severe infections and even amputation. Proper foot care is a key prevention strategy, although the effectiveness of interventions varies in practice. Objective: This study analyzes the effectiveness of foot care interventions in preventing ulcers in diabetic patients through a systematic literature review. A Systematic Literature Review was conducted following the PRISMA guidelines and the PICO approach (Population: type II diabetes patients; Intervention: foot care interventions; Comparison: standard education or no specific intervention; Outcome: prevention of foot ulcers). Article searches were conducted using the PubMed and Google Scholar databases from 2020 to 2025 using the keywords: diabetic foot care, foot ulcer prevention, and foot care education. The initial search yielded 268 articles, comprising 212 articles from Google Scholar and 56 articles from PubMed. Further screening was conducted by reading the titles and abstracts, removing duplicates and irrelevant articles, leaving 98 articles. During the eligibility stage, the full texts were thoroughly read and selected based on the established criteria, ultimately yielding 10 articles that met the criteria for further analysis. The methodological quality of the articles was assessed using the JBI Critical Appraisal Tools. A review of 10 articles showed that various interventions, including behavior-based education and technology models, were effective in improving foot care and significantly reducing the risk of ulcers (p < 0.05) across all studies.